g(

g(

f(s(

R

↳Removing Redundant Rules

Removing the following rules from

g(x,y) ->x

g(x,y) ->y

where the Polynomial interpretation:

was used.

_{ }^{ }POL(g(x)_{1}, x_{2})= 1 + x _{1}+ x_{2}_{ }^{ }_{ }^{ }POL(s(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(f(x)_{1}, x_{2}, x_{3})= 2·x _{1}+ x_{2}+ x_{3}_{ }^{ }

Not all Rules of

R

↳RRRPolo

→TRS2

↳Removing Redundant Rules

Removing the following rules from

f(s(x),y,y) -> f(y,x, s(x))

where the Polynomial interpretation:

was used.

_{ }^{ }POL(s(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(f(x)_{1}, x_{2}, x_{3})= 2·x _{1}+ x_{2}+ x_{3}_{ }^{ }

All Rules of

R

↳RRRPolo

→TRS2

↳RRRPolo

→TRS3

↳Dependency Pair Analysis

Duration:

0:00 minutes